La politique étrangère japonaise sous Nakasone : Le dilemme d’une superpuissance économique - Bedeski, Robert (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1984)
After decades of intensive economic growth Japan is under pressure to translate its material success into international influence. This new role appears to be taking shape under Prime Minister Nakasone. The country faces rising protectionism sentiments from its major trading partners, and a growing military threat from the USSR. Nakasone has maintained a solid working relation with President Reagan, while adopting a hawkish stance towards the USSR. Nevertheless, Japan still remains under the US nuclear umbrella. Nakasone has pursued closer relations with South Korea. His first foreign visit as prime minister was to Seoul. The Chinese have been concerned about symptoms of remilitarization on the one hand, but also recognize that a greated Japanese security presence will help to diffuse the Soviet threat in the region, thus relieving pressure on Beijing. The first six months of Nakasone's administration thus indicated that Japan may be embarking on a diplomatic and defence course which has a higher profile than in the past.